COLLAGEN GENE ANALYSIS IN PATIENTS WITH LOCALIZED SCLERODERMA - Muydinov O.Kh; Khayitov M.S (Scholar Express Journals, 2024)
Localized Scleroderma (LS) is a chronic connective tissue disorder that predominantly affects the skin and underlying tissues. It is marked by localized areas of sclerosis accompanied by inflammatory symptoms, such as erythema and edema, followed by skin atrophy and alterations in pigmentation (hypo- or hyperpigmentation), as noted by Kubanova in 2010. While LS can occur at any age, it often develops in a localized form, presenting with chronic inflammation and fibroatrophic skin and mucosal lesions. In recent decades, the incidence of LS has increased. Among children and adolescents, it is the most prevalent form of scleroderma, with an estimated prevalence of 1 case per 37,000 individuals. Girls are three to four times more likely than boys to be affected (Kubanova, A.N. Lev., 2013; Kreuter et al., 2006).
Keywords: Localized Scleroderma; pigmentation; erythema; tissue